Evaluation Expression COX-2 in Prostatic Carcinoma by PCR and Immunohistochemistry and Its Relationship with Gleason Score - Ghiasi, Maryam; Moradi Tabriz, Hedieh; Nazar, Elham (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: Prostate cancer is among the most common malignancies. Despite the high prevalence and importance of prostate cancer, the molecular mechanisms underlying its development and progression remain poorly understood. Materials and Methods: This cross sectional study was conducted on 50 cases of prostatic carcinoma with different Gleason score referred to Sina hospital in Tehran in Iran in 2016. The gene expression was assessed by using the immunohistochemistry staining and PCR technique. Result: The presence of neoplasia on prostatic biopsy induced strong staining and increased in mRNA level of COX-2 expression when compared to normal tissue (P-Value >0.05). The expression is not well associated with different Gleason grades of prostatic carcinoma. Conclusion: The expression of COX-2 protein by immunohistochemistry staining and PCR technique in our study offers the valuable diagnostic information. Thus, we think this marker might be studied in larger series of patients for its further validation as diagnostic factor in prostate biopsies.